Shale inhibitor and preparation method thereof
By combining chemical inhibitors and physical inhibitors, the problems of insufficient inhibitory performance of existing shale inhibitors in drilling operations and great impact on drilling fluid performance are solved, and more efficient hydration inhibition effect and better environmentally friendly performance.
Patent Information
- Application Number
- CN202411331649.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Existing shale inhibitors have problems such as insufficient inhibitory performance, great impact on drilling fluid performance, and are not environmentally friendly in drilling operations, making it difficult to effectively inhibit hydration, expansion and dispersion of shale.
Using a combination method of chemical inhibitors and physical inhibitors, chemical inhibitors include 4,4'-methylenebis(cyclohexylamine), 1-vinyl-3-ethylimidazole ammonium bromide and polyetheramine. Physical inhibitors include a mixture of modified parallol nanotubes and nanozinc titanate with nanopolystyrene.
It significantly improves the hydration inhibitory ability of shale inhibitors, expands the scope of application, enhances the high-temperature resistance and safety and environmental protection performance, and reduces the impact on the performance of the drilling fluid system.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of shale inhibitors, and specifically relates to a shale inhibitor and a preparation method thereof. Background Art
[0002] With the reduction of conventional oil and gas resources, the exploration and development of unconventional oil and gas resources are indispensable. Shale is considered to be one of the most important unconventional hydrocarbon source reservoirs in the world and has broad development prospects. The use of water-based drilling fluid to extract shale oil and gas can easily cause hydration, expansion and dispersion of shale. Shale clay hydration mainly manifests as surface hydration and osmotic hydration. Surface hydration refers to hydration caused by the adsorption of water molecules on the surface of clay crystals and the hydration of exchangeable cations between crystal layers. Osmotic hydration refers to hydration caused by water penetration caused by the difference in cation concentration between drilling fluid and clay crystal layers. Under these two hydration effects, a large number of water molecules are adsorbed on the clay flakes and surfaces, and the clay volume greatly expands and loses, thereby causing various engineering problems such as well wall instability, collapse, and drill bit mud packing. Therefore, the development of efficient shale inhibitors is an important research topic in the field of oilfield chemistry.
[0003] At present, a variety of shale inhibitors have been developed, such as inorganic salts, formates, asphalts, positive electrodes, glucose derivatives, polyols, silicates and quaternary ammonium cations. Based on these inhibitors, various drilling fluid systems have been developed and successfully applied within a certain range, but they all have different limitations. The most commonly used inorganic cation potassium ion in drilling operations has an obvious inhibitory effect, but its dosage is large, which has a significant impact on the rheology and filtration of the drilling fluid. At the same time, high concentrations of potassium ions have an adverse effect on the biological environment; asphalt inhibitors have excellent anti-collapse ability, but there is fluorescence, which is not conducive to logging and other testing work, and is not conducive to environmental protection; conventional polyols and polyols have large changes in effective content, weak inhibitory properties, and problems of viscosity increase and foaming; silicates have outstanding inhibitory properties, but when added to drilling fluids, the rheology of the drilling fluid is difficult to control. Therefore, it is imperative to develop a shale inhibitor with excellent inhibitory performance, good compatibility, strong high temperature resistance, safety and environmental protection, and little effect on the performance of the drilling fluid system. Summary of the invention
[0004] The purpose of the present invention is to provide a shale inhibitor. The shale inhibitor is a compound of a chemical inhibitor and a physical inhibitor to improve the hydration inhibition ability of the shale inhibitor. The present invention also provides a preparation method thereof.
[0005] The shale inhibitor of the present invention is composed of the following raw materials in parts by weight: 0.3-0.5 parts of 4,4'-methylenebis(cyclohexylamine), 0.16-0.18 parts of 1-vinyl-3-ethylimidazolium bromide, 0.23-0.25 parts of polyetheramine, 0.25-0.27 parts of a mixture of modified palygorskite nanotubes and nano zinc titanate, and 0.16-0.19 parts of nano polystyrene. The preparation method of the mixture of modified palygorskite nanotubes and nano zinc titanate comprises the following steps: uniformly mixing deionized water, methanol and heptadecafluorodecyltrimethoxysilane, heating to 65-68°C, adding palygorskite nanotubes and nano zinc titanate to react for 35-40 minutes, then ultrasonically dispersing, and finally stirring and reacting again at 65-68°C, cooling to room temperature, filtering, washing with anhydrous ethanol for 3-4 times, and vacuum drying to prepare a mixture of modified palygorskite nanotubes and nano zinc titanate.
[0006] in:
[0007] The molecular weight of the polyetheramine is 440, the functionality is 3, the total amine value is 6.11 mmol / g, the manufacturer is Suzhou Changke Industrial Co., Ltd., and the model is T403.
[0008] The particle size of nano polystyrene is 25 nm, the manufacturer is Beijing Dekedaojin Technology Co., Ltd., and the model is PS000025.
[0009] The mass ratio of deionized water, methanol and heptadecafluorodecyltrimethoxysilane is 1:1.2-1.25:0.3-0.32.
[0010] The mass of heptadecafluorodecyltrimethoxysilane accounts for 3.5-4.0% of the total mass of palygorskite nanotubes and nano-zinc titanate.
[0011] The mass ratio of palygorskite nanotubes to nano zinc titanate is 1:0.2-0.3.
[0012] The ultrasonic dispersion time is 15-17 minutes.
[0013] The stirring speed of the stirring reaction is 400-500 r / min, and the stirring reaction time is 1.5-1.7 h.
[0014] The vacuum drying temperature is 72-75°C, and the vacuum drying time is 8-8.5h.
[0015] The shale inhibitor described in the present invention uses a compound chemical inhibitor and a physical inhibitor to broaden the scope of use of the shale inhibitor and improve the inhibitory effect of the shale inhibitor. The chemical inhibitor used is a mixture of 4,4'-methylenebis(cyclohexylamine), 1-vinyl-3-ethylimidazolium bromide and polyetheramine, and the physical inhibitor is a mixture of modified palygorskite nanotubes and nano zinc titanate and nano polystyrene. Chemical inhibitors cannot prevent the occurrence of instability of hard and brittle mudstone, so it is necessary to compound physical inhibitors. The physical inhibitors enter the pores of the porous medium in the shallow layer of the rock under the action of the pressure difference to form a bridge plug, blocking the connection channel between the water in the drilling fluid and the inside of the rock, so as to achieve the purpose of isolating the water flow path. The 4,4'-methylenebis(cyclohexylamine), 1-vinyl-3-ethylimidazolium bromide and polyetheramine in the chemical inhibitor interact with each other, so that the shale inhibitor has the characteristics of excellent inhibitory performance and strong high temperature resistance. Among them, polyetheramine T403 has a small molecular weight, and the clay has a large adsorption amount of amine groups, which can effectively inhibit the dispersion of clay. However, polyetheramine has poor heat stability, so the addition of 4,4'-methylenebis(cyclohexylamine) and 1-vinyl-3-ethylimidazolium bromide improves the high temperature resistance and hydration inhibition ability of shale inhibitors. 4,4'-methylenebis(cyclohexylamine) forms a hydrophobic layer on the clay surface by adsorbing on the clay surface, thereby reducing the infiltration of water molecules, while 1-vinyl-3-ethylimidazolium bromide is an ionic liquid with a hydrophobic side chain and a hydrophilic skeleton, so that the inhibitor has higher efficiency and thermal stability when used in deep well or ultra-deep well drilling. Therefore, the interaction between polyetheramine T403, 4,4'-methylenebis(cyclohexylamine) and 1-vinyl-3-ethylimidazolium bromide makes the inhibitor have long-term inhibition. The mixture of modified palygorskite nanotubes and nano zinc titanate in the physical inhibitor is compounded with nano polystyrene. The mixture of modified palygorskite nanotubes and nano zinc titanate is a hard inorganic nano material, which can block tiny pore throats and cracks. Palygorskite can also participate in the formation of dense mud cakes to strengthen the plugging. Nano zinc titanate is spherical. Only a small amount of zinc titanate nanoparticles can reduce the static filtration loss of the base slurry, which has a good plugging effect. The interaction between palygorskite nanotubes and nano zinc titanate can induce a hydration and curing reaction at the reservoir temperature to generate a three-dimensional network structure with a mixture of modified palygorskite nanotubes and nano zinc titanate as the core node. The compound nano polystyrene is used because nano polystyrene has excellent elasticity, which can easily enter deeper reservoirs, block the pores and cracks of shale, and change the wettability of the shale surface by adsorbing on the shale, weakening the adsorption of water on the shale surface, thereby reducing the intrusion of the water phase. As a result, the raw materials in the physical inhibitor interact with each other, making the prepared shale inhibitor suitable for low permeability areas.
[0016] The preparation method of the shale inhibitor of the present invention comprises the following steps:
[0017] (1) preparing a mixture of modified palygorskite nanotubes and nano zinc titanate;
[0018] (2) A mixture of modified palygorskite nanotubes and nano zinc titanate and nano polystyrene are added to a mixed solution of 4,4'-methylenebis(cyclohexylamine), 1-vinyl-3-ethylimidazolium bromide and polyetheramine, and the mixture is mixed evenly to prepare a shale inhibitor.
[0019] Wherein: in step (2), the mixing temperature is 65-67° C. and the mixing time is 30-40 min.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The shale inhibitor described in the present invention uses a compound of a chemical inhibitor and a physical inhibitor to expand the application scope of the shale inhibitor, improve the inhibitory ability of the shale inhibitor, effectively inhibit the hydration expansion and dispersion of shale, and has good compatibility between the raw materials, so that the prepared shale inhibitor has higher efficiency and thermal stability during the drilling process.
[0022] (2) The shale inhibitor described in the present invention has a lower linear expansion rate and a higher rolling recovery rate, and can also reduce the static filtration loss of the base slurry.
[0023] (3) The preparation method of the shale inhibitor described in the present invention has a simple process, easy-to-control preparation parameters, and the performance of the prepared shale inhibitor is stable. DETAILED DESCRIPTION
[0024] The present invention is further described below with reference to the embodiments.
[0025] The raw material palygorskite nanotubes used in the mixture of modified palygorskite nanotubes and nano zinc titanate are prepared by the following steps:
[0026] ① After cleaning the surface of the palygorskite, dry it at 80℃ and put it into a grinder for preliminary crushing. After crushing, pass it through a 100-mesh sieve and then dry it at 80℃ for 1.5h;
[0027] ② The powder obtained in step ① is placed in a zirconia ball mill, and a Φ4 mm grinding ball is added to make the ball mass ratio 20:1. The loading amount of the palygorskite mineral in the ball mill is half of the tank body. The ball mill is placed on a ball mill, and the ball mill speed is 150 r / min. The rotation direction is alternately changed every 10 minutes. The dry-wet ball milling process is used to prepare palygorskite nanotubes. The dry ball milling is performed for 30 hours and the wet ball milling is performed for 30 hours. During the wet ball milling, the ratio of the ethanol capacity to the tank volume is 1:4, and palygorskite nanotubes are prepared.
[0028] The manufacturer of the raw material nano zinc titanate used in the mixture of modified palygorskite nanotubes and nano zinc titanate is Qinghe Chaotai Metal Materials Co., Ltd.
[0029] Example 1
[0030] The shale inhibitor described in Example 1 is composed of the following raw materials in parts by weight: 0.4 parts of 4,4'-methylenebis(cyclohexylamine), 0.17 parts of 1-vinyl-3-ethylimidazolium bromide, 0.24 parts of polyetheramine, 0.26 parts of a mixture of modified palygorskite nanotubes and nano-zinc titanate, and 0.18 parts of nano-polystyrene. The preparation method of the mixture of modified palygorskite nanotubes and nano-zinc titanate comprises the following steps: uniformly mixing deionized water, methanol and heptadecafluorodecyltrimethoxysilane, heating to 66°C, adding palygorskite nanotubes and nano-zinc titanate to react for 38 minutes, then ultrasonically dispersing, and finally stirring and reacting again at 66°C, cooling to room temperature, filtering, washing with anhydrous ethanol 4 times, and vacuum drying to prepare a mixture of modified palygorskite nanotubes and nano-zinc titanate.
[0031] in:
[0032] The molecular weight of the polyetheramine is 440, the functionality is 3, the total amine value is 6.11 mmol / g, the manufacturer is Suzhou Changke Industrial Co., Ltd., and the model is T403.
[0033] The particle size of nano polystyrene is 25 nm, the manufacturer is Beijing Dekedaojin Technology Co., Ltd., and the model is PS000025.
[0034] The method for preparing palygorskite nanotubes comprises the following steps:
[0035] The mass ratio of deionized water, methanol, and heptadecafluorodecyltrimethoxysilane is 1:1.23:0.31.
[0036] The mass of heptadecafluorodecyltrimethoxysilane accounts for 3.7% of the total mass of palygorskite nanotubes and nano-zinc titanate.
[0037] The mass ratio of palygorskite nanotubes to nano zinc titanate is 1:0.25.
[0038] The ultrasonic dispersion time was 16 min.
[0039] The stirring speed of the stirring reaction is 450 r / min, and the stirring reaction time is 1.6 h.
[0040] The vacuum drying temperature was 74°C and the vacuum drying time was 8.3 h.
[0041] Example 2
[0042] The shale inhibitor described in Example 2 is composed of the following raw materials in parts by weight: 0.5 parts of 4,4'-methylenebis(cyclohexylamine), 0.16 parts of 1-vinyl-3-ethylimidazolium bromide, 0.23 parts of polyetheramine, 0.25 parts of a mixture of modified palygorskite nanotubes and nano-zinc titanate, and 0.16 parts of nano-polystyrene. The preparation method of the mixture of modified palygorskite nanotubes and nano-zinc titanate comprises the following steps: uniformly mixing deionized water, methanol and heptadecafluorodecyltrimethoxysilane, heating to 68°C, adding palygorskite nanotubes and nano-zinc titanate to react for 35 minutes, then ultrasonically dispersing, and finally stirring and reacting again at 68°C, cooling to room temperature, filtering, washing with anhydrous ethanol three times, and vacuum drying to prepare a mixture of modified palygorskite nanotubes and nano-zinc titanate.
[0043] in:
[0044] The molecular weight of the polyetheramine is 440, the functionality is 3, the total amine value is 6.11 mmol / g, the manufacturer is Suzhou Changke Industrial Co., Ltd., and the model is T403.
[0045] The particle size of nano polystyrene is 25 nm, the manufacturer is Beijing Dekedaojin Technology Co., Ltd., and the model is PS000025.
[0046] The mass ratio of deionized water, methanol, and heptadecafluorodecyltrimethoxysilane is 1:1.20:0.30.
[0047] The mass of heptadecafluorodecyltrimethoxysilane accounts for 3.5% of the total mass of palygorskite nanotubes and nano-zinc titanate.
[0048] The mass ratio of palygorskite nanotubes to nano zinc titanate is 1:0.2.
[0049] The ultrasonic dispersion time was 15 min.
[0050] The stirring speed of the stirring reaction is 400 r / min, and the stirring reaction time is 1.5 h.
[0051] The vacuum drying temperature is 72°C and the vacuum drying time is 8 h.
[0052] Example 3
[0053] The shale inhibitor described in Example 3 is composed of the following raw materials in parts by weight: 0.3 parts of 4,4'-methylenebis(cyclohexylamine), 0.18 parts of 1-vinyl-3-ethylimidazolium bromide, 0.25 parts of polyetheramine, 0.27 parts of a mixture of modified palygorskite nanotubes and nano-zinc titanate, and 0.19 parts of nano-polystyrene. The preparation method of the mixture of modified palygorskite nanotubes and nano-zinc titanate comprises the following steps: uniformly mixing deionized water, methanol and heptadecafluorodecyltrimethoxysilane, heating to 65°C, adding palygorskite nanotubes and nano-zinc titanate to react for 40 minutes, then ultrasonically dispersing, and finally stirring and reacting again at 65°C, cooling to room temperature, filtering, washing with anhydrous ethanol 4 times, and vacuum drying to prepare a mixture of modified palygorskite nanotubes and nano-zinc titanate.
[0054] in:
[0055] The molecular weight of the polyetheramine is 440, the functionality is 3, the total amine value is 6.11 mmol / g, the manufacturer is Suzhou Changke Industrial Co., Ltd., and the model is T403.
[0056] The particle size of nano polystyrene is 25 nm, the manufacturer is Beijing Dekedaojin Technology Co., Ltd., and the model is PS000025.
[0057] The mass ratio of deionized water, methanol, and heptadecafluorodecyltrimethoxysilane is 1:1.25:0.32.
[0058] The mass of heptadecafluorodecyltrimethoxysilane accounts for 4.0% of the total mass of palygorskite nanotubes and nano-zinc titanate.
[0059] The mass ratio of palygorskite nanotubes to nano zinc titanate is 1:0.3.
[0060] The ultrasonic dispersion time was 17 min.
[0061] The stirring speed of the stirring reaction is 500 r / min, and the stirring reaction time is 1.7 h.
[0062] The vacuum drying temperature was 75°C and the vacuum drying time was 8.5 h.
[0063] Comparative Example 1
[0064] The preparation method of the shale inhibitor described in this comparative example 1 is the same as that of Example 1, and the only difference is that the raw material composition is different from that of Example 1. The shale inhibitor described in this comparative example 1 is composed of the following raw materials in parts by weight: 0.4 parts of 4,4'-methylenebis(cyclohexylamine), 0.17 parts of 1-vinyl-3-ethylimidazolium bromide, and 0.24 parts of polyetheramine.
[0065] Comparative Example 2
[0066] The preparation method of the shale inhibitor described in this comparative example 2 is the same as that of Example 1, and the only difference is that the raw material composition is different from that of Example 1. The shale inhibitor described in this comparative example 2 is composed of the following raw materials in parts by weight: 0.26 parts of a mixture of modified palygorskite nanotubes and nano zinc titanate, and 0.18 parts of nano polystyrene, wherein the preparation method of the mixture of modified palygorskite nanotubes and nano zinc titanate is the same as that of Example 1.
[0067] In order to further illustrate the effect of the shale inhibitor prepared by the present invention, the shale inhibitors in Examples 1-3 and Comparative Examples 1-2 were tested in terms of linear expansion rate and rolling recovery rate. The shale inhibitors prepared in Examples 1-3 and Comparative Examples 1-2 were mixed with deionized water at a mass ratio of 2% for the experiment. Deionized water was used as a reference. The test standard was the petroleum and natural gas industry standard SY / T 5613-2016 Drilling Fluid Test "Test Method for Physical and Chemical Properties of Mud Shale". The high temperature conditions for the rolling recovery rate test were aging temperature 200°C and aging time 16h. The test results are shown in Table 1 below:
[0068] Table 1 Shale inhibitor performance test results
[0069]
[0070] According to the provisions of GB / T 16783.1-2014, the effects of different shale inhibitors prepared in Examples 1-3 and Comparative Examples 1-2 on the API filtration loss of bentonite-based slurry were tested. The preparation method of the bentonite-based slurry was as follows: 400 mL of distilled water was added to a high-speed stirring cup, 0.69 g of anhydrous sodium carbonate and 20.0 g of bentonite for drilling fluid test slurry were slowly added in sequence while stirring, and the mixture was stirred at a speed of 8000 r / min for 20 min, during which the mixture was interrupted 4 times to scrape the bentonite on the cup wall and the blades into the base slurry, and the mixture was sealed and cured at 25° C. for 24 h to obtain the bentonite-based slurry. The test results are shown in Table 2 below.
[0071] Table 2 API filtration loss test results of shale inhibitors of Examples 1-3 and Comparative Examples 1-2
[0072]
[0073] As shown in Table 1, the linear expansion rate of the shale inhibitors prepared in Examples 1-3 of the present invention is significantly lower than that in Comparative Examples 1-2, and the rolling recovery rate is significantly higher than that in Comparative Examples 1-2. The lower the linear expansion rate and the higher the rolling recovery rate, the better the inhibition performance of the shale inhibitor. Therefore, it can be seen that the shale inhibitors prepared in this application have excellent inhibition performance. As shown in Table 2, the shale inhibitors prepared in Examples 1-3 of the present invention can also reduce the static filtration loss of the base slurry compared with Comparative Examples 1-2, and have a good plugging effect.
Claims
1. A shale inhibitor, characterized in that: The method comprises the following raw materials in parts by weight: 0.3-0.5 parts of 4,4'-methylenebis(cyclohexylamine), 0.16-0.18 parts of 1-vinyl-3-ethylimidazolium bromide, 0.23-0.25 parts of polyetheramine, 0.25-0.27 parts of a mixture of modified palygorskite nanotubes and nano zinc titanate, and 0.16-0.19 parts of nano polystyrene. The method for preparing the mixture of modified palygorskite nanotubes and nano zinc titanate comprises the following steps: uniformly mixing deionized water, methanol and heptadecafluorodecyltrimethoxysilane, heating to 65-68° C., adding palygorskite nanotubes and nano zinc titanate to react for 35-40 minutes, then ultrasonically dispersing, and finally stirring and reacting again at 65-68° C., cooling to room temperature, filtering, washing with anhydrous ethanol for 3-4 times, and vacuum drying to prepare a mixture of modified palygorskite nanotubes and nano zinc titanate; in: The mass ratio of deionized water, methanol, and heptadecafluorodecyltrimethoxysilane is 1:1.2-1.25:0.3-0.32; The mass of heptadecafluorodecyltrimethoxysilane accounts for 3.5-4.0% of the mass of palygorskite nanotubes and nano-zinc titanate; The mass ratio of palygorskite nanotubes to nano zinc titanate is 1:0.2-0.
3.
2. The shale inhibitor according to claim 1, characterized in that: The molecular weight of the polyetheramine is 440, the functionality is 3, and the total amine value is 6.11 mmol / g.
3. The shale inhibitor according to claim 1, characterized in that: The ultrasonic dispersion time is 15-17 minutes.
4. The shale inhibitor according to claim 1, characterized in that: The stirring speed of the stirring reaction is 400-500 r / min, and the stirring reaction time is 1.5-1.7 h.
5. The shale inhibitor according to claim 1, characterized in that: The vacuum drying temperature is 72-75°C, and the vacuum drying time is 8-8.5h.
6. A method for preparing the shale inhibitor according to claim 1, characterized in that: It consists of the following steps: (1) preparing a mixture of modified palygorskite nanotubes and nano zinc titanate; (2) A mixture of modified palygorskite nanotubes and nano zinc titanate and nano polystyrene are added to a mixed solution of 4,4'-methylenebis(cyclohexylamine), 1-vinyl-3-ethylimidazolium bromide and polyetheramine, and the mixture is mixed evenly to prepare a shale inhibitor.
7. The method for preparing a shale inhibitor according to claim 6, characterized in that: In step (2), the mixing temperature is 65-67° C. and the mixing time is 30-40 min.
Citation Information
Patent Citations
Alkylated polyetheramines as clay stabilizing agents
CN104540920A
Polyurea silicate resin for wellbore application
CN104870599A